2022
DOI: 10.1049/itr2.12181
|View full text |Cite
|
Sign up to set email alerts
|

Improved longitudinal control strategy for connected and automated truck platoon against cyberattacks

Abstract: With the conception of internet of vehicle, the longitudinal control strategy of connected and automated truck platoon (CATP) to effectively deal with threat of cyberattacks has become an urgent challenge. Based on this, by flexibly changing the communication topology of truck platoon, this paper designs a communication topology safety response system (CTSRS), and further combined with the distributed model predictive control (DMPC) method, an improved longitudinal control strategy of CATP is tentatively propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The Corrected Akaike Information Criterion (AICc) and the coefficient of determination (R 2 ) were used to evaluate the fit of our model. AICc and R 2 are calculated as follows [32,33]:…”
Section: Evaluation Metricsmentioning
confidence: 99%
“…The Corrected Akaike Information Criterion (AICc) and the coefficient of determination (R 2 ) were used to evaluate the fit of our model. AICc and R 2 are calculated as follows [32,33]:…”
Section: Evaluation Metricsmentioning
confidence: 99%
“…Noei et al [ 12 ] proposed a traffic microsimulation tool that can simulate conventional, automated, and connected and automated vehicles in a platoon under fault, failure, and cyberattack with optimized accuracy and simulation speed to maximize throughput and without compromising safety or string stability. Lyu et al [ 13 ] designed a communication topology safety response system (CTSRS), and further combined with the distributed model predictive control (DMPC) to ensure the stability and security of the truck platoon even if the trucks suffer cyberattacks. Cheng et al [ 14 ] proposes a novel intelligent driving model considering cyberattacks and heterogeneous vehicles and revealed that the traffic stability and safety under cyber-attacks can be enhanced through the high proportion of cars and the information accepted from cooperative vehicles ahead.…”
Section: Introductionmentioning
confidence: 99%